To the question about definition of the notion «Special operations of the bodies of internal affairs» (Journal of actual problems of jurisprudence, 2019)
The article deals with such an aspect of the administrative activities of the internal affairs bodies as the organization and conduct of special operations. The author explores the problems of defining the basic terms in this field. A clear understanding of the concept, content and types of special operations of the internal affairs bodies is necessary not only for organizing the effective work of the law enforcement system, but also for ensuring the rights and freedoms of individuals and legal entities. Special operations of the internal affairs bodies a priori imply the use of force to solve problem situations; they are inevitably linked to the widespread use of measures of state coercion. Accordingly, the special operations of the internal affairs bodies directly affect the constitutional rights and freedoms of the citizens involved.The author addresses in his work the problem of the definition of the very notion «special operations». At the same time, the article presents the opinions of various scientists regarding the definition and classification of special operations carried out by the internal affairs bodies. It should be noted that the concept of special operations is not fixed in the current legislation of the Republic of Kazakhstan. According to the author, this concept should be reflected in the Law «On the Internal Affairs Bodies of the Republic of Kazakhstan». Justifying his position, the author also proposes his definition, reflecting themain features of the special operation of the internal affairs bodies.Key words: special operation, law enforcement agencies, state coercion, methods of administrativeactivity, forms of administrative activity.